2022
DOI: 10.3390/tropicalmed7120423
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Mixed Studies on Malaria in Pregnancy: Individual, Cultural and Socioeconomic Determinants of Its Treatment and Prevention

Abstract: Malaria in pregnancy (MiP) is a global public health problem; its research is predominantly quantitative. The objective was to analyze the individual, cultural and socioeconomic determinants of the treatment and prevention of MiP with a systematic review of mixed studies (search had no date restriction). Reproducibility and evaluation of the methodological quality were guaranteed. 21 studies were included (20 from Africa). The quantitative component included 7816 pregnant women and 483 health workers. The qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…This situation has also been described in the qualitative component of mixed studies on MiP, and a systematic review of QHR in MiP that reported lacking knowledge about MiP and its consequences, lacking perception of the risk of becoming infected, and poor knowledge about prevention [ 6 , 7 ]. This demonstrates multiple challenges for health education, information and communication programmes, since the individual cognitive dimension in this population is determined by social, cultural and economic processes, which are excluded in this type of health strategy, despite having a greater explanatory power on individual behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation has also been described in the qualitative component of mixed studies on MiP, and a systematic review of QHR in MiP that reported lacking knowledge about MiP and its consequences, lacking perception of the risk of becoming infected, and poor knowledge about prevention [ 6 , 7 ]. This demonstrates multiple challenges for health education, information and communication programmes, since the individual cognitive dimension in this population is determined by social, cultural and economic processes, which are excluded in this type of health strategy, despite having a greater explanatory power on individual behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the advances in QHR, critical approaches are scarce, and phenomenological-hermeneutic studies predominate [ 1 ]. Regarding MiP there are no studies about PSDH and most QHR focus on content (frequency of concepts or words to infer meanings) or thematic (focused in pre-established categories) analysis about acceptability barriers of insecticide-treated bed nets, intermittent preventive treatment or case management [ 6 , 7 ]. There is no social study of MiP in Colombia or America, that allows an initial identification of their PSDH.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies carried out in Colombia using qualitative analysis allow malaria to be approached as a problem from the perspective of the social determinants of health, grouped as structural determinants (the origin of malaria, its relation to life and work conditions, and the importance of home and family) and individual determinants (traditional knowledge about paludism, the importance of knowledge secularization about malaria and the perception of different communities about the risk of infection and death from malaria) (Cardona-Arias et al, 2019;Cardona-Arias et al, 2020;Cardona-Arias, 2022). Here, our work aimed to use qualitative analysis to understand the perceptions of the residents about: malaria risk areas, their own problems, the solutions proposed by themselves and how those solutions are related to the strategies proposed in the official programs from health institutions.…”
Section: Community Perspectives About Malaria Control and Elimination...mentioning
confidence: 99%
“…In this review, 48 qualitative studies were included with 2600 pregnant women, 1300 HWs, and 2200 relatives and community members; the most frequent topics were the meanings, perceptions and behaviors on MiP, SP-IPTp, ITN and case management, which is similar to a systematic review on mixed studies about MiP [80].…”
Section: Main Findingsmentioning
confidence: 99%
“…In the first group, this and other reviews recognized MiP as a risk event but pregnant women do not perceive their vulnerability to this disease. Local interpretations overlap the symptoms and consequences of MiP with other febrile syndromes or are assumed as conditions inherent to pregnancy, and there is preference for the diagnosis and treatment over prevention [20,21,80]. Attitudes and behaviors related to MiP interventions are associated with attitudes and interactions with HWs, the organization of health services, and experiences of poor health care [20,21,23].…”
Section: Saturated Qualitative Evidencementioning
confidence: 99%